An Analysis of Code Mixing Used by Sacha Stevenson’s Conversation “House Tour” - Luh Gede Kumala, Dewi; I Dewa Ayu Devi Maharani Santika (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
This study delves into code mixing in the conversation